Penggunaan Media Audio Visual Dalam Keterampilan Menulis Teks Fabel Kelas VII MTs Darul Ulum Sipaho - Aulia, Putri; Rambe, Riris Nurkholidah (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
This research aims to improve fable text writing skills using audio-visual media for class VII students at MTs Darul Ulum Sipaho. This type of research is quantitative research with a pre-experimental method, the research design used is one group pretest-posttest. This research procedure includes preparation, implementation and completion. The subjects in this research were class VII students at MTs Darul Ulum Sipaho. totaling 36 people. The results of research and statistical data analysis show that the average pretest and posttest scores using audio-visual media in learning to write fable texts are 54 and 82.05. Furthermore, inferential statistical analysis of the t-test results obtained that thirung is 8.873 and ttable is 1.689 at a significance level of 0.05 or 5% so tcount (8.873) > ttable (1.689) means H0 is rejected and H1 is accepted, so the hypothesis is accepted. In the N-Gain test, students' ability to write fable texts using audio-visual media at the interval g ≥ 0.7 can be analyzed in the high category. Based on the results of the research above, it can be concluded that fable text writing skills influence the use of audio-visual media on class VII fable writing skills at MTs Darul Ulum Sipaho.